2019
DOI: 10.1111/bjso.12351
|View full text |Cite
|
Sign up to set email alerts
|

Rules of engagement: Reactions to internal and external criticism in public debate

Abstract: Since 2014, the refugee crisis has launched a political shockwave across Europe, with consequences for the European Union, the Schengen Zone, and national politics. Within this context, we investigated how public statements about the refugee crisis are received. While debate and criticism are hallmarks of a democratic society, research demonstrates that people respond more negatively to criticism about their group from an outsider compared with an insider. But does this reflect a protective bias in favour of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 27 publications
1
24
3
Order By: Relevance
“…Furthermore, the normative acceptability of stigmatization has been shown to vary as a function of direct and indirect measures of political tolerance of stigmatized minority groups (Brown-Iannuzzi et al, 2019). In addition, several experimental studies have demonstrated that people apply double standards when determining the acceptability of critical speech with people being more tolerant of critical speech from a member of the criticized group (i.e., an Arab American criticizing Arabs, a native Dutch person criticizing native Dutch, or a refugee criticizing refugees) rather than an out-group member doing the same (Adelman & Verkuyten, 2020b; Lindner & Nosek, 2009). Intolerance arising from intuitive objection is particularly vulnerable to double standards, as the absence of clarity on the objection itself, makes it more likely for double standards to go unnoticed.…”
Section: Intuitive and Deliberative Intolerancementioning
confidence: 99%
“…Furthermore, the normative acceptability of stigmatization has been shown to vary as a function of direct and indirect measures of political tolerance of stigmatized minority groups (Brown-Iannuzzi et al, 2019). In addition, several experimental studies have demonstrated that people apply double standards when determining the acceptability of critical speech with people being more tolerant of critical speech from a member of the criticized group (i.e., an Arab American criticizing Arabs, a native Dutch person criticizing native Dutch, or a refugee criticizing refugees) rather than an out-group member doing the same (Adelman & Verkuyten, 2020b; Lindner & Nosek, 2009). Intolerance arising from intuitive objection is particularly vulnerable to double standards, as the absence of clarity on the objection itself, makes it more likely for double standards to go unnoticed.…”
Section: Intuitive and Deliberative Intolerancementioning
confidence: 99%
“…Importantly, these results are only to be expected when the criticism is directed at the ingroup. As shown by Adelman and Verkuyten (2020), outgroup critics are evaluated more positively than ingroup critics when their criticism is directed at the outgroup. These results suggest that outgroup critics are not rejected because of their outgroup identity per se, but because they are assumed to be less knowledgeable and constructive.…”
Section: Introductionmentioning
confidence: 96%
“…Across three high‐powered experiments, Adelman and Verkuyten (2020) compared two classic ISE conditions (i.e., ingroup target: ingroup source vs. outgroup source) with two outgroup target conditions (i.e., outgroup target: ingroup source vs. outgroup source). In line with a norm explanation, they found that ingroup members targeting the outgroup also elicited rejection of the message, lower ratings of constructiveness, and lower approval of the commenter's actions in self‐reports.…”
Section: Introductionmentioning
confidence: 99%
“…We thus term the resulting effect the pure bystander effect . In contrast, Adelman and Verkuyten (2020) investigated criticism by an ingroup member targeted at the outgroup in their bystander conditions. Because these bystander conditions involve a group member criticizing an outgroup, social identity and normative concerns could jointly motivate defensive responses (cf.…”
Section: Introductionmentioning
confidence: 99%